International Approaches to Professional Development for Mathematics Teachers - Atinuke Y Adeyemi (University of Windsor, 2015)
This book provides a rich description of the experiences and innovative approaches established in various countries to support the professional development of practising mathematics teachers. Many of these approaches are based on classroom context and considered the practitioners' viewpoints. The analyses in various chapters help elucidate how the approaches articulate with practice, the contributions of teachers and teacher educators/researchers, and the fundamental theoretical framework directing the researchers. The chapters cover various aspects, including the main trends and issues in the education of practising mathematics teachers, the changes in their role during their careers, the learning that occur between teachers and teacher educators/researchers, and the hidden power relations in the collaboration between the two groups. There are indications that the formal and informal experiences of mathematics teachers, all through their careers, can contribute to their professional development and that the viewpoints of teachers and their practical knowledge must be genuinely considered in order to construct critical professional development experiences. In essence, the book offers new ways of creating continuous professional development that would help bridge the gap between research and practice.